ARENA THEATER AND THE DEVELOPMENT OF A BRA ZILIAN WAY OF INTERPRETING (Olhares, 2025)
São Paulo`s Teatro de Arena, founded in 1953 by José Renato Pécora, with the initialobjective of trying out a new and cheaper way of doing theater. Then developed its history toexperience a brazilian way to do it and looking for a nationalist theater that was in opposition tothe elitist model of the time carried out by the Teatro Brasileiro de Comédia. One of the essentialelements for thinking about a Brazilian way of doing theater was to develop, at the same time, aBrazilian way of acting. Actresses and actors from the group gave their testimonies, seeking topresent the different ways of doing that developed throughout the rehearsals and shows thatguided this search for a “ genuine Brazilian actor”. Teatro de Arena leaves a legacy both in theconstruction of a Brazilian way of acting and in the elaboration of a dramaturgy that mirrored thenational reality.
Keywords: Teatro de Arena; acting; brazilian theatre; Augusto Boal